Gebox Media to Facilitate the Cognitive Development of Children Aged 5-6 Years on Geometry Concepts - Edi Hendri Mulyana; Dindin Abdul Muiz Lidinillah; Fina Latifah (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine the feasibility obtained from Gebox Learning Media. In the process, the Educational Design Research (EDR) method was used, with the McKenney and Reeves models, resulting in a three-dimensional learning media called Gebox. In the stages the steps taken in this study consist of 7 parts, namely; (1) Preliminary study and field study, (2) Determine competence and learning indicators, (3) Formulate learning objectives. (4) Outline the media, (5) Create products, (6) Product validation, (7) Product trials. This Gebox learning media is considered suitable for use by experts, and gets a good response when used in learning. Gebox media is believed to have a good contribution in helping to facilitate cognitive development for children aged 5-6 years on the concept of geometry. With the Gebox media, it is hoped that learning about the introduction of geometry concepts can run actively, meaningfully, and interestingly.